Development of a drone‐borne electromagnetic survey system for searching for buried vehicles and soil resistivity mapping. Issue 1 (27th December 2021) - Mitsuhata, Yuji; Ueda, Takumi; Kamimura, Akiya; Kato, Shin; Takeuchi, Atsushi; Aduma, Chikara; Yokota, Toshiyuki
ABSTRACT: We developed a drone‐borne electromagnetic survey system using a commercial multi‐frequency electromagnetic sensor equipped with a GPS receiver, a WiFi serial transceiver, and an ultrasonic distance sensor to measure the height of the electromagnetic sensor above the ground surface. The electromagnetic sensor was suspended from a drone with ropes. The distance between the drone and the electromagnetic sensor was adjusted to minimize the influence of electromagnetic noise generated by the drone, and to stabilize the electromagnetic sensor during flight. The system was tested at two experimental sites. The first site consisted of two buried vehicles to simulate a landslide. We assumed a scenario in which the search for the buried vehicles was urgent and accessibility to the area was limited. The second site consisted of wet and dry agricultural fields to test resistivity mapping. In the first test, we used the in‐phase component of the measured data to locate the vehicles. The shallower vehicle was identified clearly, while the deeper vehicle was located successfully, albeit less easily. In the second test, the quadrature component was used for one‐dimensional inversion after data processing, which included data smoothing, resampling and bias noise correction. The bias noise was measured while hovering the drone at a high altitude to negate the influence of ground conductivity. The results showed that the resistivity distributions could be mapped at some depths by using a five‐frequency‐processed quadrature component, and clearly showed the difference between the wet and dry fields. The crucial parameter in the evaluations of these targets was the height of the electromagnetic sensor above the ground surface, which was measured continuously during flight. The results demonstrated the potential of the survey system to search for buried metal objects and for shallow subsurface resistivity mapping over relatively large areas.